Structure, Total Synthesis, and Biosynthesis of Chloromyxamides: Myxobacterial Tetrapeptides Featuring an Uncommon 6‐Chloromethyl‐5‐methoxypipecolic Acid Building Block. Issue 43 (1st October 2018) - Gorges, Jan; Panter, Fabian; Kjaerulff, Louise; Hoffmann, Thomas; Kazmaier, Uli; Müller, Rolf
Abstract: Soil‐living microbes are an important resource for the discovery of new natural products featuring great structural diversity that are reflective of the underlying biosynthetic pathways as well as incorporating a wide range of intriguing small‐molecule building blocks. We report here the full structural elucidation, total synthesis, and biosynthesis of chloromyxamides, a new class of tetrapeptides that display an unprecedented 6‐chloromethyl‐5‐methoxypipecolic acid (CMPA) substructure. Chemical synthesis—including an approach to access the CMPA unit—was pursued to confirm the structure of the chloromyxamides and enabled determination of the absolute configuration in the CMPA ring. A model for the nonribosomal assembly of chloromyxamides was devised on the basis of the combined evaluation of the biosynthetic gene cluster sequence and the feeding of stable isotope‐labeled precursors. This provided insight into the formation of the various chloromyxamide derivatives and the biogenesis of the CMPA unit. Abstract : Family matters : A family of chlorinated tetrapeptides called chloromyxamides have been discovered from myxobacteria and their structure fully elucidated. The study features a concise chemical synthesis and a model for chloromyxamide biosynthesis, underpinned by stable isotope labeling and tandem‐MS experiments.